Chemical and Biological Treatment of Plastic Wastes by Bacteria Isolated from Contaminated Soils in Baghdad, Iraq - Hussein, Amal A; Alzuhairi, Mohammed; Aljanabi, Noor H (Al-Nahrain Journal of Science, 2018)
Due to the rapid increasing of polyethylene terephthalate (PET) used in industries, there are large of wastes quantities inter the stream per year which make a serious problem to water environment. In this work, the chemical treatment involve plastic bottles pieces mixed with MgO nano-catalyst, the result was white powder of polyethylene terephthalate (PET) which was used in this study. This work aims to isolate and screen bacterial isolates that able to degrade PET powder. Thirty eight bacterial isolates have been isolated from different waste disposal sites in Baghdad city. These isolates were screened on minimal salt media (MSM) plates according to clear zone method and the change in indicator color by using PET powder as the sole source of carbon and energy. According to morphological, biochemical characteristic, and analysis by Vitek 2 the most active isolates were identified as Acinetobacter baumannii.